Export Diversification and Economic Growth - Hesse, Heiko (World Bank, Washington, DC, 2017)
Export diversification can lead to higher growth. Developing countries should diversify their exports since this can, for example, help them to overcome export instability or the negative impact of terms of trade in primary products. The process of economic development is typically a process of structural transformation where countries move from producing "poor-country goods" to "rich-country goods." Export diversification does play an important role in this process. The author also provides robust empirical evidence of a positive effect of export diversification on per capita income growth. This effect is potentially nonlinear with developing countries benefiting from diversifying their exports in contrast to the most advanced countries that perform better with export specialization.